Surf Life Saving the official website of Surf Lifesaving Australia. - Surf Life Saving Australia (Rosebury, N.S.W. : Surf Life Saving Australia)
"Surf Life Saving is Australia's major water safety, drowning prevention and rescue authority. We create a safe environment on Australia's beaches and coastline through patrols, education and training, public safety campaigns and the promotion of health and fitness."
Title from title screen (viewed on 12 July 2012 )
Text and graphics.
Mode of access: Available online. Address as at 23/08/2012
Selected for archiving
Keywords: Surf Life Saving Australia; Lifesaving -- Australia; Surf lifesaving (Aquatic sports) -- Australia; Australian